Keratoconus patients exhibit a distinct ocular surface immune cell and inflammatory profile - D’Souza, Sharon; Nair, Archana Padmanabhan; Sahu, Ganesh Ram; Vaidya, Tanuja; Shetty, Rohit; Khamar, Pooja; Mullick, Ritika; Gupta, Sneha; Dickman, Mor M.; Nuijts, Rudy M. M. A.; Mohan, Rajiv R.; Ghosh, Arkasubhra; et al. (Scientific reports, 2021)
Inflammatory factors have been considered to contribute to keratoconus (KC) pathogenesis. This study aims to determine the immune cells subsets and soluble inflammatory factor profile on the ocular surface of KC patients. 32 KC subjects (51 eyes) across different grades of severity and 15 healthy controls (23 eyes) were included in the study. Keratometry and pachymetry measurements were recorded. Ocular surface immune cells (collected by ocular surface wash) immunophenotyped using flow cytometry include leukocytes, neutrophils, macrophages, natural killer (NK) cells, pan-T cells, gamma delta T (γδT) cells and NKT cells. Tear fluid collected using Schirmer’s strip was used to measure 50 soluble factors by multiplex ELISA. Proportions of activated neutrophils, NK cells and γδT cells were significantly increased in KC patients. Significantly higher levels of tear fluid IL-1β, IL-6, LIF, IL-17A, TNFα, IFNα/β/γ, EPO, TGFβ1, PDGF-BB, sVCAM, sL-selectin, granzyme-B, perforin, MMP2, sFasL and IgE, along with significantly lower levels of IL-1α and IL-9 were observed in KC patients. Alterations observed in few of the immuno-inflammatory parameters correlated with grades of disease, allergy, eye rubbing and keratometry or pachymetry measurements. The observation implies a distinct immuno-inflammatory component in KC pathogenesis and its potential as an additional therapeutic target in KC management.